FEATURES OF MOTIVATION OF MILITARY PERSONNEL TO MILITARY PROFESSIONAL ACTIVITIES - Vitaliia Ihorivna Shebanova; Hanna Olehivna Nikitenko (Insight: the psychological dimensions of society, 2019)
The article deals with the urgent problem of motivation for military activity. The theoretical analysis of scientific literature indicates that the motivation for military-professional activity of military personnel is a complex system of motives that activates and directs the person to professional activity.Purpose. The aim of the article is to present the results of the study of features of motives for joining military service and features of motivation of servicemen with different military service experience. An empirical sample included of 126 military personnel by persons, ranging in age from 20 to 46 years.Methods. In order to study the peculiarities of the motivational component of the structure of psychological readiness of military personnel for military professional activity, we used the author’s questionnaire "Determining the influence of internal and external factors on the psychological readiness of mobilized persons to military service". Among the methods of mathematical and statistical data processing, Student’s t-criterion for independent measurements, the Z-transform procedure and factor analysis have been used.Results. It has been found out that the motivational component that exerts a systematic influence on the internal and external factors of the structure of psychological readiness of military personnel through the implementation of stimulating, regulatory and meaning-forming functions. It has been established that the main motives for joining the military are: self-realization, recognition, patriotism (desire to defend the Motherland) and solving personal problems. It has been found out that the greater military service experience; the more likely there are positive thoughts on the news of the call. Persons with experience of contract service demonstrate a more positive attitude to military service, the importance of its passage; have a higher level of motivation to perform military professional activity than persons without experience of military service.Conclusions. The positive attitude towards the professional activity of the military, the internal motivation, the general level of psychological readiness for military service increases with service experience.